The origins of deconstruction - McQuillan, Martin; Willis, Ika, 1975- (Basingstoke, UK : Palgrave MacMillan, 2010)
'In these essays, a range of leading scholars seek both to investigate the historical, institutional and philosophical origins of deconstruction and to think through the problem of the idea of origin itself'--Provided by publisher
Introduction : the origins of deconstruction : Derrida's daughters / Ika Willis -- Dating : deconstruction / Marc Froment-Meurice -- The course of a general displacement, or, the course of the choreographer / Lynn Turner -- Feminine endings : Dido's telephonic body and the originary function of the hymen / Ika Willis -- On prejudice and foretelling 2 / Thomas Docherty -- Extremes meet / Jean-Michel Rabate -- The opening to infinity : Derrida's quasi-transcendentals -- Splitting the origin : writing and responsibility / Margret Grebowicz -- Derridean beginning and Deleuzian becomiong / Paul Patton --'Words of air' : on breath and inspiration / Claudia Baracchi -- Illegibility : on the spirit of origins / John P. Leavey, Jr. -- Origins of deconstruction? : deconstruction, that which arrives (if it arrives) / Julian Wolfreys -- Philosophy of cinders and cinders of philosophy : a commentary on the origins of deconstruction and the Holocaust / Robert Englestone -- The beginnings of art : Heidegger and Bataille / Gerard Bucher -- Aesthetic allegory : reading Hegel after Bernal / Martin McQuillian
Includes bibliographical references and index
Keywords: Deconstruction; Aesthetics; Art -- Philosophy